Low retarding polycarboxylic acid gypsum water reducing agent and preparation method thereof

CN122940403APending Publication Date: 2026-10-20SHAANXI JINGCHENG BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611085095.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-21
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0007]本发明的主要目的在于提供一种低缓凝聚羧酸石膏减水剂及其制备方法,以至少解决现有技术中石膏减水剂低缓凝特性与抗杂质絮凝性能难以兼顾,适配工业副产石膏稳定性差的问题

Benefits of technology

[0024]本发明技术方案的一种低缓凝聚羧酸石膏减水剂及其制备方法,按重量百分比计,包括:异戊烯醇聚氧乙烯醚20.0~24.0,丙烯酸4.0~5.5,马来酸酐1.0~1.5,甲基丙烯酸甲酯0.6~0.9,过硫酸盐0.35~0.50,次亚磷酸钠0.30~0.40,有机膦酸螯合剂1.2~2.0,氢氧化钠水溶液17.0~19.5,余量为去离子水,各组分重量百分比之和为100%。通过由异戊烯醇聚氧乙烯醚、丙烯酸、马来酸酐与甲基丙烯酸甲酯共同构成聚羧酸分散体系,在赋予石膏颗粒优异减水分散效果的同时,避免对石膏水化进程产生过度阻滞;由过硫酸盐与次亚磷酸钠复配协同调控聚合物分子量及分布,保障浆体分散均匀性与作用长效性,避免局部缓凝偏重与后期絮凝问题;由低掺量有机膦酸螯合剂优先络合体系内游离钙离子与杂质金属离子,提升产品对杂质波动较大的工业副产石膏的适配稳定性,且不会加剧石膏缓凝副作用;辅以氢氧化钠水溶液精准调控体系pH,优化分子分散活性与储存稳定性。整套配方从分散效能、抗杂能力、水化调控、体系稳定多个维度,解决了传统石膏聚羧酸减水剂低缓凝特性与抗杂质絮凝性能难以兼顾的技术瓶颈,有效改善工业副产石膏浆体易絮凝结块、生产连续性差、批次适配性弱的缺陷,在保证优异减水分散效果的同时维持石膏正常凝结硬化速率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

This invention provides a low-deceleration carboxylic acid gypsum water-reducing agent and its preparation method. By weight percentage, it comprises: 20.0-24.0% isopentenyl alcohol polyoxyethylene ether, 4.0-5.5% acrylic acid, 1.0-1.5% maleic anhydride, 0.6-0.9% methyl methacrylate, 0.35-0.50% persulfate, 0.30-0.40% sodium hypophosphite, 1.2-2.0% organophosphonic acid chelating agent, 17.0-19.5% sodium hydroxide aqueous solution, and the balance being deionized water. The sum of the weight percentages of all components is 100%. The isopentenyl alcohol polyoxyethylene ether, acrylic acid, maleic anhydride, and methyl methacrylate copolymerize to form a dispersion system, exhibiting both excellent water-reducing and dispersion effects and low hydration retardation characteristics. Persulfate and sodium hypophosphite ensure long-term uniform dispersion of the slurry. A low dosage of organophosphonic acid chelating agent improves the compatibility with industrial by-product gypsum without exacerbating retardation, and the sodium hydroxide aqueous solution regulates the pH of the system. This solution overcomes the technical bottleneck of simultaneously achieving low retardation and resistance to impurity flocculation, and is adapted to the high-efficiency production needs of precast gypsum building materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of water-reducing agent technology, and more specifically, to a low-slow-coagulation carboxylic acid gypsum water-reducing agent and its preparation method. Background Technology

[0002] With the large-scale application of gypsum-based building materials in precast components, building plastering, and self-leveling flooring, the resource utilization of industrial by-product gypsum has become a core direction for the industry's green development. my country produces tens of millions of tons of industrial by-product gypsum such as desulfurized gypsum and phosphogypsum annually. After calcination, these can replace natural building gypsum in industrial production. However, industrial by-product gypsum generally contains impurities such as soluble sulfates, phosphates, and free calcium ions. Furthermore, the impurity content varies greatly between different origins and batches of raw materials, placing stringent requirements on the compatibility of gypsum water-reducing agents.

[0003] Polycarboxylate superplasticizers, with their advantages of high water reduction rate and good environmental performance, have gradually replaced traditional naphthalene-based and lignin-based superplasticizers, becoming the mainstream product in gypsum building material admixtures. However, most existing general-purpose polycarboxylate superplasticizers are developed with cement systems as the compatibility benchmark, and their direct application to gypsum systems has obvious compatibility defects: the hydration rate of gypsum is much faster than that of cement, the ionic environment of the systems is significantly different, the adsorption behavior of general-purpose superplasticizers in gypsum slurry is unstable, and the effective dispersion time is short. Especially in industrial by-product gypsum systems containing soluble impurities, free calcium and sulfate ions in the slurry will prematurely consume the effective components of the superplasticizer, resulting in the superplasticizer not being able to act evenly on the surface of gypsum particles. After stirring, the slurry quickly flocculates and clumps, and the inner walls of the mixing tank and conveying pipelines are severely adhered and scaled. The production line needs to be stopped for cleaning 2 to 3 times per shift, resulting in poor continuous production stability and high equipment maintenance and manual cleaning costs.

[0004] To address the issue of slurry flocculation and agglomeration, the industry's conventional approach is to compound retarder components such as citric acid and sodium gluconate into the water-reducing agent. This extends the dispersion maintenance time by slowing down the hydration rate of gypsum. While this method can alleviate slurry agglomeration to some extent, it significantly prolongs the gypsum setting time, resulting in slow early strength development of the product and a greatly extended demolding cycle. This makes it unsuitable for the high-speed production rhythm of gypsum boards, decorative molds, and precast blocks, directly restricting capacity expansion. Furthermore, the effectiveness of the retarder is highly dependent on impurity content, and the retarding range is difficult to control precisely when raw material batches fluctuate. This can easily lead to over-retardation, softened and sandy product surfaces, or even prolonged periods without solidification, resulting in a significant decrease in the finished product qualification rate.

[0005] Currently, some polycarboxylate superplasticizers specifically for gypsum have appeared on the market, but their technical approaches generally lean towards high retarding and high plasticity retention. They are mainly suitable for scenarios requiring a long construction window, such as gypsum self-leveling and large-area plastering mortar, and cannot meet the core requirements of precast component production for low retarding, early strength, and rapid demolding. A few gypsum superplasticizers that emphasize low retarding properties only achieve short setting times by weakening the hydration retardation effect. They generally have not been specifically optimized for the interference of impurities in industrial by-product gypsum, and have weak resistance to impurity ion interference. They can only be used with high-purity natural building gypsum. When applied to industrial by-product gypsum, their dispersion stability drops sharply, and flocculation and agglomeration problems occur frequently. They cannot support the large-scale disposal and utilization of industrial by-product gypsum, nor can they achieve the dual goals of comprehensive resource utilization and improved production efficiency.

[0006] Overall, existing gypsum water-reducing agent technologies have always faced a technical contradiction between low retarding properties and resistance to impurity flocculation, making it impossible to simultaneously meet the multiple requirements of mass application of industrial by-product gypsum, high-speed demolding on production lines, and stable and continuous production processes. Developing a gypsum-specific water-reducing agent that combines the advantages of low retarding with strong resistance to impurity flocculation is a common technical problem that the industry urgently needs to solve. Summary of the Invention

[0007] The main objective of this invention is to provide a low-slow-coagulation carboxylic acid gypsum water-reducing agent and its preparation method, so as to at least solve the problem that the existing gypsum water-reducing agents have difficulty in simultaneously achieving low-slow-coagulation characteristics and anti-flocculation performance, and have poor stability when used with industrial by-product gypsum.

[0008] To achieve the above objectives, the present invention provides a low-deceleration carboxylic acid gypsum water-reducing agent, comprising, by weight percentage:

[0009] The composition comprises: isopentenyl alcohol polyoxyethylene ether 20.0~24.0, acrylic acid 4.0~5.5, maleic anhydride 1.0~1.5, methyl methacrylate 0.6~0.9, persulfate 0.35~0.50, sodium hypophosphite 0.30~0.40, organophosphonic acid chelating agent 1.2~2.0, sodium hydroxide aqueous solution 17.0~19.5, and the balance being deionized water. The sum of the weight percentages of all components is 100%. Optionally, the persulfate is one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0010] Optionally, the organophosphonic acid chelating agent is at least one of 2-aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and ethylenediaminetetramethylidenephosphonic acid.

[0011] Optionally, the persulfate has a particle size range of 80 mesh to 120 mesh;

[0012] The sodium hypophosphite has a particle size range of 100 mesh to 140 mesh.

[0013] This invention also provides a method for preparing a low-delay coagulation carboxylic acid gypsum water-reducing agent, used in the low-delay coagulation carboxylic acid gypsum water-reducing agent of this invention, the preparation method comprising the following steps:

[0014] Bottom material dissolution: Add the specified amount of isopentenyl alcohol polyoxyethylene ether and part of deionized water to the reactor, heat to 60~65℃, and stir until completely dissolved to obtain the bottom material liquid;

[0015] Preparation of solutions: Prepare a mixed monomer aqueous solution containing acrylic acid, maleic anhydride and methyl methacrylate, a first aqueous solution containing persulfate, and a second aqueous solution containing sodium hypophosphite.

[0016] Copolymerization reaction: The bottom liquid in the reactor is continuously controlled at 60~65℃, and the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution are simultaneously added dropwise to the bottom liquid in the reactor; after the addition is completed, the temperature is maintained for polymerization for 2~2.5h to obtain polycarboxylate mother liquor;

[0017] Low-temperature curing: The polycarboxylic acid mother liquor in the reactor is cooled to 45~55℃, and the appropriate amount of organophosphonic acid chelating agent is added to the reactor. The mixture is kept warm and stirred for 1.5~2 hours.

[0018] Neutralization and stabilization: Cool the material in the reactor to 40~45℃, add the appropriate amount of sodium hydroxide aqueous solution to the reactor and adjust the pH to 7.2~7.8;

[0019] Volumetric discharge: Add the remaining deionized water to the reactor, homogenize, filter, and obtain low-coagulation carboxylic acid gypsum water-reducing agent.

[0020] Optionally, in the solution preparation step, when preparing the mixed monomer aqueous solution, maleic anhydride is first completely dissolved in water, and then acrylic acid and methyl methacrylate are added and mixed to dissolve.

[0021] Optionally, during the copolymerization reaction step, the reactor is kept under negative pressure throughout the synchronous dropwise addition process, with a negative pressure value of -0.03 to -0.01 MPa.

[0022] Optionally, in the copolymerization step, the dropping rate ratio of the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution is 5:1:1.

[0023] Optionally, after filtration in the volumetric discharge step, the mixture is stirred and homogenized at room temperature for 25-35 minutes, and then sealed and allowed to stand for 10-14 hours.

[0024] The present invention discloses a low-coagulation carboxylic acid gypsum water-reducing agent and its preparation method, comprising, by weight percentage: 20.0-24.0% isopentenyl alcohol polyoxyethylene ether, 4.0-5.5% acrylic acid, 1.0-1.5% maleic anhydride, 0.6-0.9% methyl methacrylate, 0.35-0.50% persulfate, 0.30-0.40% sodium hypophosphite, 1.2-2.0% organophosphonic acid chelating agent, 17.0-19.5% sodium hydroxide aqueous solution, and the balance being deionized water, wherein the sum of the weight percentages of all components is 100%. A polycarboxylic acid dispersion system composed of isopentenyl polyoxyethylene ether, acrylic acid, maleic anhydride, and methyl methacrylate imparts excellent water-reducing and dispersing effects to gypsum particles while avoiding excessive inhibition of the gypsum hydration process. The synergistic regulation of polymer molecular weight and distribution by the compounding of persulfate and sodium hypophosphite ensures uniform dispersion and long-lasting effect of the slurry, avoiding localized overemphasis on retarding and subsequent flocculation problems. A low-dosage organic phosphonic acid chelating agent preferentially complexes free calcium ions and impurity metal ions within the system, improving the product's compatibility and stability with industrial by-product gypsum exhibiting significant impurity fluctuations, without exacerbating the retarding side effects of gypsum. Furthermore, the precise pH control of the system using sodium hydroxide aqueous solution optimizes molecular dispersion activity and storage stability. The entire formula addresses the technical bottleneck of traditional gypsum polycarboxylate superplasticizers, which struggle to balance low setting and impurity flocculation resistance, from multiple dimensions including dispersion efficiency, anti-impurity ability, hydration regulation, and system stability. It effectively improves the defects of industrial by-product gypsum slurry, such as easy flocculation and agglomeration, poor production continuity, and weak batch compatibility, while maintaining the normal setting and hardening rate of gypsum and ensuring excellent water-reducing and dispersing effects. Attached Figure Description

[0025] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0026] Figure 1 This is a flowchart of a method for preparing a low-coagulation carboxylic acid gypsum water-reducing agent, which is optional according to an embodiment of the present invention. Detailed Implementation

[0027] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. The present invention will now be described in detail with reference to the accompanying drawings and embodiments.

[0028] This application provides a low-deceleration carboxylic acid gypsum water-reducing agent, comprising, by weight percentage:

[0029] The composition is: isopentenyl alcohol polyoxyethylene ether 20.0~24.0, acrylic acid 4.0~5.5, maleic anhydride 1.0~1.5, methyl methacrylate 0.6~0.9, persulfate 0.35~0.50, sodium hypophosphite 0.30~0.40, organophosphonic acid chelating agent 1.2~2.0, sodium hydroxide aqueous solution 17.0~19.5, with the balance being deionized water. The sum of the weight percentages of all components is 100%.

[0030] Specifically, isopentenyl alcohol polyoxyethylene ether, as a macromolecular side-chain monomer, constructs the main framework and steric hindrance structure of the polycarboxylic acid polymer. The selection of a medium molecular weight (2300~2800) polyether structure ensures excellent gypsum particle dispersion while avoiding excessive adsorption of long side chains on the gypsum crystal surface and hydration hindrance caused by multi-layer coating. This reduces the retarding side effect from the molecular structure root, ensuring a balance between the basic fluidity and hydration progress of the gypsum slurry. Acrylic acid and maleic anhydride, as hydrophilic functional monomers, provide appropriate carboxyl adsorption sites for the polymer molecular chain, endowing the product with excellent dispersion and water-reducing capabilities for gypsum particles. Combined with a small amount of hydrophobic methyl methacrylate monomer copolymerization, it effectively reduces the overall carboxyl density of the polymer molecular chain, weakens the adsorption and coverage strength of the polymer on the gypsum crystal surface, avoids excessive hydration inhibition caused by high carboxyl density, and achieves a synergistic match between water-reducing performance and low retarding performance.

[0031] Persulfate, as a thermally decomposable initiator, can stably generate free radicals under polymerization temperature conditions to initiate monomer copolymerization. Sodium hypophosphite, as a highly efficient chain transfer agent, works synergistically with the other to precisely control the molecular weight and molecular weight distribution of the polymer, narrowing the molecular size distribution range of the product. This avoids the problems of uneven adsorption and localized slow coagulation caused by ultra-high molecular weight components in the system, while also preventing the late-stage flocculation of the slurry caused by the rapid failure of low molecular weight components, thus significantly improving the dispersion stability and hydration uniformity of gypsum slurry.

[0032] Organophosphonic acid chelating agents possess excellent complexing ability between calcium ions and metal impurities. Industrial by-product gypsum systems are rich in free calcium ions, soluble sulfates, and trace metal impurities, which readily consume the effective components of polycarboxylic acid and induce slurry flocculation and agglomeration. The low-dosage organophosphonic acid chelating agent specified in this invention can preferentially complex free active calcium ions and impurity ions within the system, blocking the side reactions of impurity ions interfering with the adsorption and dispersion of polycarboxylic acid, and improving the product's compatibility and stability with industrial by-product gypsum where impurities fluctuate greatly. Simultaneously, controlling the low dosage avoids the defect of excessive calcium ion complexation caused by high-dosage phosphonic acid components, which exacerbates gypsum setting delay, achieving a balance between anti-flocculation and low-retarding properties. The dosage of the organophosphonic acid chelating agent described in this invention is based on the mass of the effective active ingredient.

[0033] The sodium hydroxide aqueous solution has a mass concentration of 30%~35% and is used for precise pH control of the system after polymerization. This stabilizes the acid-base environment of the mother liquor in the weakly neutral range, optimizes the ionization state of polycarboxylic acid molecules, improves molecular dispersion activity and storage stability, and avoids product performance degradation caused by acid-base imbalance.

[0034] Deionized water, as a dispersion medium, is free from interference by metal impurity ions, providing a stable and clean reaction environment for polymerization reactions and the compounding of various functional components. This ensures uniform dispersion and stable compatibility of the functional components, avoiding polymerization anomalies, product stratification during storage, and performance fluctuations induced by water impurities.

[0035] This invention utilizes a polycarboxylic acid dispersion system composed of isopentenyl polyoxyethylene ether, acrylic acid, maleic anhydride, and methyl methacrylate. This system imparts excellent water-reducing and dispersing effects to gypsum particles while avoiding excessive inhibition of the gypsum hydration process. The synergistic regulation of polymer molecular weight and distribution by a combination of persulfate and sodium hypophosphite ensures uniform dispersion and long-lasting effects, preventing localized over-regulation and subsequent flocculation problems. A low-dosage organic phosphonic acid chelating agent preferentially complexes free calcium ions and impurity metal ions within the system, improving the product's compatibility and stability with industrial by-product gypsum exhibiting significant impurity fluctuations without exacerbating the gypsum's retarding side effects. Furthermore, the precise pH control of the system using sodium hydroxide aqueous solution optimizes molecular dispersion activity and storage stability. The entire formula addresses the technical bottleneck of traditional gypsum polycarboxylate superplasticizers, which struggle to balance low setting and impurity flocculation resistance, from multiple dimensions including dispersion efficiency, anti-impurity ability, hydration regulation, and system stability. It effectively improves the defects of industrial by-product gypsum slurry, such as easy flocculation and agglomeration, poor production continuity, and weak batch compatibility, while maintaining the normal setting and hardening rate of gypsum and ensuring excellent water-reducing and dispersing effects.

[0036] In one possible implementation, the persulfate is one of ammonium persulfate, sodium persulfate, and potassium persulfate.

[0037] Specifically, ammonium persulfate, sodium persulfate, and potassium persulfate are all commonly used water-soluble, thermally decomposable free radical initiators. They are chemically stable at room temperature, do not easily decompose spontaneously, and are highly safe for storage and preparation. They are completely soluble in water to form a homogeneous and transparent initiator aqueous solution, without insoluble residues or stratification. They exhibit excellent compatibility with water-based water-reducing agent systems. When heated, these persulfates can uniformly break down to generate free radicals, which can stably initiate the copolymerization reaction of unsaturated monomers. The initiation process is gradual and the reaction starts mildly, avoiding the localized explosive polymerization and cross-linking side reactions caused by a sudden burst of large amounts of free radicals. This ensures the polymerization reaction proceeds gradually and stably. Furthermore, the decomposition products of these persulfates are non-toxic and harmless inorganic sulfate systems, containing no toxic organic intermediates. They do not introduce impurity ions into the gypsum system, do not interfere with the gypsum hydration and crystallization process, and do not cause problems such as abnormal flocculation, discoloration, or uncontrolled slow setting in the slurry. The advantages of using the above-mentioned persulfate are: moderate initiation activity and a wide controllable reaction range, which can ensure the stable and orderly synthesis process of polycarboxylic acid polymers and the uniform and regular molecular structure of the polymers prepared; the system is clean and residue-free, which is suitable for the low impurity and high stability preparation requirements of gypsum-based building materials, and can effectively improve the dispersion uniformity and batch stability of the water-reducing agent, avoid product performance fluctuations caused by system disorder, and greatly improve the compatibility and stability of the water-reducing agent with gypsum slurry.

[0038] In one possible implementation, the organophosphonic acid chelating agent is at least one of 2-aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and ethylenediaminetetramethylidene phosphonic acid.

[0039] Specifically, 2-aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and ethylenediaminetetramethylidene phosphonic acid are all water-soluble organic phosphonic acid chelating components. Their molecular structures carry multiple phosphonic acid coordination groups. The oxygen atoms of the phosphonic acid groups can provide lone pairs of electrons to form stable five-membered ring coordination chelates with metal ions such as calcium, iron, magnesium, and manganese ions. These complexes have strong binding forces and high coordination stability constants. Industrial by-product gypsum raw material systems continuously dissolve large amounts of free calcium ions, accompanied by trace amounts of transition metal impurities. Free calcium ions readily bind to the carboxyl active sites on the polycarboxylic acid molecular chains, directly consuming the effective dispersing components in the water-reducing agent, causing rapid flocculation and agglomeration of gypsum slurry particles. Transition metal ions also catalyze oxidation side reactions of active oxygen-containing substances in the system, destroying the complete molecular chain structure of polycarboxylic acid and causing a rapid decline in the dispersion performance of the finished product. These three organophosphonic acid molecules can preferentially coordinate and complex with various metal ions in the system, pre-fix various interfering ions, block the ineffective binding reaction between metal ions and polycarboxylic acid molecules, and eliminate slurry flocculation defects caused by ion imbalance from the source.

[0040] This type of organophosphonic acid is a weakly retarding calcium ion complexing agent. Compared with conventional high-retarding organophosphonates, it does not continuously bind a large number of calcium ions at the same addition ratio, and does not significantly inhibit the precipitation and crystal growth of gypsum dihydrate crystal nuclei. While completing ion complexation and impurity removal, it can maintain the normal hydration rhythm of gypsum itself. At the same time, the three components have excellent water solubility and can be miscible with the water-based system of water-reducing agents in any proportion. They are not prone to crystallization during long-term storage at room temperature, and have excellent compatibility and stability with the other components in the formula. Relying on its strong metal ion complexing ability, it can significantly improve the adaptability of water-reducing agents to industrial by-product gypsum with large fluctuations in impurity content, effectively solving the problem of slurry flocculation and agglomeration. In addition, its own weak hydration retardation effect on gypsum can simultaneously take into account the two core properties of anti-flocculation and low retarding. Moreover, there is no stratification or crystallization phenomenon during storage, ensuring that the performance of water-reducing agents is consistent between different production batches.

[0041] In one possible implementation, the persulfate has a particle size range of 80 mesh to 120 mesh;

[0042] The sodium hypophosphite has a particle size range of 100 mesh to 140 mesh.

[0043] Specifically, in this invention, the persulfate particle size ranges from 80 mesh to 120 mesh, and the sodium hypophosphite particle size ranges from 100 mesh to 140 mesh.

[0044] Persulfate is only prepared as an aqueous solution and added to the reactor during the early stage of polymerization. This substance has moderate thermal decomposition sensitivity and does not require an extremely high dissolution rate; a relatively coarse range of 80-120 mesh is used. Excessive fineness would significantly increase the risk of hygroscopic decomposition of the powder, leading to premature deactivation during storage and disrupting the supply of free radicals for polymerization. This particle dissolution rate is moderate, allowing for rapid preparation of a uniform initiator solution while minimizing the probability of self-degradation during storage, stabilizing the release rhythm of free radicals in the early stage of polymerization, and avoiding slow-release fluctuations caused by deviations in molecular weight distribution.

[0045] Sodium hypophosphite, as the core chain transfer component for controlling molecular weight, needs to participate uniformly throughout the long-term dropwise copolymerization process. It has the highest requirements for dissolution uniformity and instantaneous concentration stability; therefore, a finer particle size range of 100-140 mesh is selected. Smaller particles have a larger specific surface area, allowing for instantaneous and complete dissolution during dropwise addition. This ensures a consistently uniform concentration of the chain transfer agent throughout the reactor, continuously and stably constraining the polymer chain length and effectively reducing the formation of ultra-high molecular weight byproducts. It also avoids excessive retardation caused by the large-scale adsorption of gypsum crystals by high molecular weight components from the source. While this raw material has weak antioxidant capacity and fine particles are easily oxidized, the molecular weight control benefits from uniform dissolution during the on-demand feeding mode far outweigh short-term oxidation losses, making it suitable for the continuous dropwise addition process.

[0046] If the overall particle size of the powder is too large, the particle specific surface area is small, and the water dissolution rate is slow, problems such as delayed particle dissolution and incomplete dissolution of local powders are likely to occur when preparing aqueous solutions. Uneven concentrations of initiators and chain transfer agents will appear in the reaction system, leading to inconsistent rates of free radical release during copolymerization, disordered chain transfer regulation, and ultimately a wider molecular weight distribution of the synthesized polycarboxylate polymer, with a mixture of high and low molecular weight components in the system. Ultra-high molecular weight components are prone to excessive adsorption and coating on the surface of gypsum crystals, causing severe local hydration hindrance and excessive retardation; low molecular weight components have poor adsorption stability and are prone to rapid failure, causing flocculation and decreased dispersion retention of gypsum slurry in the later stages, ultimately resulting in an inability to stably achieve both low retardation and anti-flocculation performance of the product. If the powder particle size is too fine and the specific surface area is too large, the raw materials are extremely prone to moisture absorption, agglomeration, and even premature deterioration during storage. Persulfate ultrafine powder is prone to premature decomposition and release of free radicals after absorbing moisture, leading to activity decay and inactivation. Sodium hypophosphite ultrafine powder is easily oxidized and deactivated upon contact with air, losing its ability to precisely control molecular weight through chain transfer, resulting in uncontrolled molecular structure of the polymerization product. In addition, the production of ultrafine powders generates a lot of dust and has poor operability, which is not conducive to stable industrial production.

[0047] By matching the optimal particle size range for each functional powder, and differentiating the dissolution requirements and storage limitations of three types of materials, the dissolution rate and reaction process of each powder are highly compatible. This allows for the rapid formation of a homogeneous and stable aqueous solution, ensuring uniform release of free radicals and continuous and stable chain transfer throughout the polymerization process. It enables precise and controllable synthesis of well-defined polycarboxylic acid molecules with narrow molecular weight distribution and low carboxyl adsorption density, stabilizing the product's core low-retardation performance from the polymerization source. Powders with moderate particle size exhibit good storage stability and are less prone to moisture absorption and deterioration. They are easy to add and have high proportioning accuracy, effectively ensuring high consistency in molecular structure, dispersion performance, and coagulation control performance across different production batches of water-reducing agents. This significantly improves the product's compatibility and stability in complex impurity systems of industrial by-product gypsum, consistently achieving excellent water-reducing dispersion, controllable retardation, and no flocculation or agglomeration.

[0048] This invention also provides a method for preparing a low-delay coagulation carboxylic acid gypsum water-reducing agent, used to prepare the low-delay coagulation carboxylic acid gypsum water-reducing agent of this invention, the preparation method comprising the following steps:

[0049] S1. Bottom material dissolution: Add the proportioned amount of isopentenyl alcohol polyoxyethylene ether and part of deionized water to the reactor, heat to 60~65℃, and stir until completely dissolved to obtain the bottom material liquid.

[0050] S2. Preparation of solution: Prepare a mixed monomer aqueous solution containing acrylic acid, maleic anhydride and methyl methacrylate, a first aqueous solution containing persulfate, and a second aqueous solution containing sodium hypophosphite.

[0051] S3. Copolymerization reaction: The temperature of the bottom liquid in the reactor is continuously controlled at 60~65℃. The mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution are simultaneously added dropwise to the bottom liquid in the reactor. After the addition is completed, the temperature is maintained for polymerization for 2~2.5h to obtain polycarboxylate mother liquor.

[0052] S4. Low-temperature curing: Cool the polycarboxylic acid mother liquor in the reactor to 45~55℃, add the specified amount of organophosphonic acid chelating agent to the reactor, and keep it warm and stir for 1.5~2 hours.

[0053] S5. Neutralization and Stabilization: Cool the material in the reactor to 40~45℃, add the appropriate amount of sodium hydroxide aqueous solution to the reactor and adjust the pH to 7.2~7.8;

[0054] S6. Volumetric discharge: Add the remaining deionized water to the reactor for homogenization, filter, and obtain low-coagulation carboxylic acid gypsum water-reducing agent.

[0055] Specifically, S1, base material dissolution

[0056] Add the specified amount of isopentenyl alcohol polyoxyethylene ether and a portion of deionized water into the reactor at once. Start mechanical stirring and maintain a stable stirring speed of 220-260 r / min. Slowly raise the temperature of the system at a rate of 0.8-1.2℃ / min, and finally maintain a constant temperature of 60-65℃. Stir at this constant temperature for 90-120 minutes until the material is completely transparent and clear, with no agglomerated particles or sediment at the bottom of the reactor. This step limits the dissolution temperature to 60-65℃. This temperature range allows the large molecular weight isopentenyl alcohol polyoxyethylene ether to fully expand and hydrate, avoiding high-temperature chain scission degradation or low-temperature agglomeration and sedimentation. It forms a uniform and continuous reaction substrate, ensuring uniform material diffusion when adding monomers and initiators later. This ensures uniform copolymerization from the fundamental reaction level, which is conducive to the synthesis of polycarboxylic acid molecules with balanced carboxyl group distribution and concentrated molecular weight. It reduces gypsum hydration hindrance from the molecular level, stabilizes the product's low-retardation core properties, and ensures complete dissolution at this temperature by setting a constant stirring speed and sufficient stirring time.

[0057] S2, Preparation of liquid feed

[0058] Three independent solutions were prepared under normal temperature and pressure conditions. The stirring speed was controlled at 150-180 r / min, and each solution was stirred for 30-40 min. A mixed monomer aqueous solution containing acrylic acid, maleic anhydride, and methyl methacrylate, a first aqueous solution containing persulfate, and a second aqueous solution containing sodium hypophosphite were prepared. After preparation, each solution was allowed to stand for 20 min and stored separately. Preparing the three solutions independently avoids premature contact between the initiator and chain transfer agent, preventing quenching side reactions and preserving their ability to regulate the polymerization molecular weight. This prevents a broadened molecular weight distribution that could lead to localized slow setting and excessive flocculation of the gypsum paste in the later stages.

[0059] S3, copolymerization reaction

[0060] The reactor is kept at a constant temperature of 60-65℃ throughout the process, with stirring maintained at 240-280 rpm. The mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution are added simultaneously and continuously, with the total addition time controlled at 3.5-4.5 hours. After addition, polymerization is carried out at this temperature for 2-2.5 hours. The constant temperature range is matched to the stable free radical decomposition characteristics of persulfate. Simultaneous addition allows monomers, initiators, and chain transfer agents to participate in chain growth in real time. Combined with prolonged temperature holding, this significantly improves monomer conversion, synthesizing a well-defined polycarboxylate matrix with a narrow molecular weight distribution. This reduces the retardation and aggravation problems caused by the large amount of gypsum crystals coated with ultra-high molecular weight components. The fixed stirring speed within the reactor ensures uniform mixing of the materials at all times.

[0061] S4, Low-temperature ripening

[0062] After the copolymerization reaction is completed, the temperature is lowered to 45-55℃ at a rate of 0.6-1.0℃ / min and kept constant. The stirring speed is reduced to 180-220 r / min. After adding the specified amount of organophosphonic acid chelating agent, stirring is continued for 1.5-2 hours. After polymerization, the temperature is lowered to 45-55℃ before adding the organophosphonic acid chelating agent, and the temperature is kept constant for 1.5-2 hours to avoid side reactions between the chelating agent and residual free radicals in the system at high temperatures, thus preserving the chelating activity. Adding the chelating agent after cooling can fully preserve its ability to complex metal ions. The maturation process allows the chelating agent to fully integrate with the polycarboxylic acid system. Relying on the weak calcium ion blocking properties of phosphonic acid, it can complex free calcium and metal impurities in industrial by-product gypsum and avoid slurry flocculation without further aggravating the retardation of gypsum setting.

[0063] S5, Neutralization and Stabilization

[0064] After maturation, the temperature is reduced to 40-45℃ at a rate of 0.6-1.0℃ / min, and the stirring speed is adjusted to 160-200 r / min. Sodium hydroxide aqueous solution is slowly added dropwise to adjust the pH to 7.2-7.8. Low-temperature neutralization avoids the strong alkali hydrolysis at high temperature, which damages the polycarboxylic acid molecular chain. The weakly neutral range of 7.2-7.8 optimizes the ionization state of polycarboxylic acid, taking into account both dispersion activity and storage stability. The constant stirring speed throughout the process is only to ensure that the system is mixed evenly after the alkali solution is added.

[0065] S6, Volumetric discharge

[0066] Maintain stirring at 140-170 rpm at room temperature, add the remaining deionized water, and continue homogenizing for 50-70 minutes. After homogenization, filter through a 100-mesh filter to obtain the finished water-reducing agent. After adding the remaining deionized water to make up the volume, filter again. Precisely fixing the concentration of the effective components in the finished product with water replenishment ensures that the low-retarding and anti-flocculation properties of each batch of products are consistent. Filtration can remove trace amounts of agglomerated colloids and prevent local component enrichment that could cause uneven gypsum setting.

[0067] In one possible implementation, during the preparation of the liquid mixture, when preparing the mixed monomer aqueous solution, maleic anhydride is first completely dissolved in water, and then acrylic acid and methyl methacrylate are added and mixed to dissolve.

[0068] Specifically, when preparing the mixed monomer aqueous solution, maleic anhydride is first added and completely dissolved in water. After the system becomes homogeneous and transparent, acrylic acid and methyl methacrylate are added sequentially for mixing and dissolution. The stirring speed is maintained at 150-180 r / min throughout the preparation process, and the stirring and dissolution time for each stage is controlled to be more than 30 minutes. Maleic anhydride molecules contain active anhydride groups, which are prone to local pre-crosslinking side reactions when directly contacting the two unsaturated monomers, acrylic acid and methyl methacrylate. Once multiple monomers are mixed simultaneously, unhydrolyzed anhydride groups will prematurely polymerize with the double bonds of other monomers, generating a small amount of short-chain crosslinking impurities. These impurities will increase the overall molecular weight distribution width of the polymer, ultimately causing localized slow setting abnormalities and decreased dispersion stability in the gypsum system. By first adding water and stirring separately to fully hydrolyze and open the ring of maleic anhydride to convert it into a dicarboxylic acid structure, the active anhydride sites in the system are completely eliminated. There are no longer active groups in the system that are prone to premature side reactions. At this time, acrylic acid and methyl methacrylate are added. Only the active double bonds required for copolymerization are retained between the three monomers, and no ineffective crosslinking byproducts are generated in the pre-preparation stage.

[0069] The stepwise dissolution method ensures that the three monomers coexist in a stable monomer form in the aqueous solution. When they are added dropwise to participate in the copolymerization in the reactor, the ratio of each monomer is stable and the functional groups on the molecular chain are evenly arranged. This accurately realizes the preset low carboxyl density molecular structure design, stably maintains the product's low retardation core characteristics, and avoids slurry flocculation and batch performance fluctuations caused by pre-crosslinked impurities.

[0070] In one possible implementation, during the copolymerization reaction step, the reactor is kept under negative pressure throughout the synchronous dropwise addition process, with a negative pressure value of -0.03 to -0.01 MPa.

[0071] Specifically, throughout the entire process of simultaneously adding the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution, a micro-negative pressure environment of -0.03 to -0.01 MPa is continuously maintained inside the reactor. Its core function has two aspects:

[0072] First, continuously removing oxygen from the system weakens the oxygen inhibition effect. Oxygen is a typical inhibitor of free radical polymerization. Oxygen molecules can rapidly combine with chain free radicals to generate low-activity peroxy free radicals, leading to prolonged polymerization induction period, fluctuating reaction rates, and a wider distribution of polymer molecular weight. Ultimately, this results in batch-to-batch instability in product dispersion performance and retarding degree. Maintaining a slight negative pressure in this range continuously removes air from the gas phase inside the reactor, reducing the dissolved oxygen content in the liquid phase. This ensures a stable and controllable polymerization reaction throughout, with uniform free radical generation and chain growth rates. This is beneficial for synthesizing polycarboxylic acid products with concentrated molecular weight distribution and regular molecular structure, ensuring batch-to-batch stability of the product's low retarding performance from the source of polymerization. It also avoids problems such as excessive local high molecular weight components and uneven gypsum hydration inhibition caused by oxygen inhibition.

[0073] Secondly, the system utilizes a top-mounted condenser for the directional recovery of volatile monomers. Under copolymerization conditions of 60-65℃, low-boiling-point unsaturated monomers such as acrylic acid will volatilize upon heating. In an atmospheric pressure system, volatile monomers tend to accumulate in the gas phase region at the top of the reactor, undergoing random self-polymerization to generate cross-linking impurities. This also alters the actual monomer ratio in the liquid phase, disrupting the pre-designed low-carboxyl-density molecular structure. Maintaining a slight negative pressure guides the volatile monomer vapors to flow directionally to the top-mounted condenser. After condensation, the monomers are reliquefied and returned to the liquid phase of the reactor to participate in the reaction. This ensures accurate monomer ratios throughout the reaction process, prevents the generation of gas-phase self-polymerization impurities, further narrows the polymer molecular weight distribution, and improves the product's compatibility and stability with industrial by-product gypsum.

[0074] This negative pressure range is within the micro-negative pressure range, and will not change the concentration of the liquid due to excessive air extraction that removes a large amount of water from the system. It can achieve the dual effects of deoxidation and stable polymerization and condensation and recovery of monomers without disrupting the material balance. Ultimately, it synthesizes a polycarboxylic acid matrix with uniform carboxyl group distribution and concentrated and regular molecular weight. It stabilizes the comprehensive performance of the water-reducing agent with high dispersion and low retardation from the copolymerization stage, and reduces the performance differences between different production batches.

[0075] In one possible implementation, during the copolymerization step, the dropping rate ratio of the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution is 5:1:1.

[0076] Specifically, during the simultaneous dropping stage, the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution are dropped at a ratio of 5:1:1. Under a constant temperature of 60-65℃, the polyether substrate continuously provides the side chain backbone for chain growth. The monomer is the core raw material for constructing the carboxyl density of the polymer molecular chain. The initiator relies on the release of free radicals through uniform decomposition to initiate the chain growth reaction. The chain transfer agent regulates the molecular chain length in real time. Maintaining a 5:1:1 dropping rate ratio ensures that the unsaturated monomer, free radicals, and chain transfer active substances in the system always maintain a dynamic equilibrium concentration, preventing any component from being instantaneously excessive or deficient. If this ratio is broken, excessively rapid monomer dropping will cause localized enrichment of carboxyl groups in the molecular chain and an increase in the degree of retardation in the finished product. Excessive initiator can easily lead to a rapid explosion of a large number of free radicals, generating ultra-high molecular weight polymers. Insufficient chain transfer agent will cause the molecular chains to stretch unrestrainedly, both of which will broaden the molecular weight distribution and destroy the low-retardation effect. A stable 5:1:1 drop acceleration rate can ensure that the growth environment of each polymer molecular chain is completely consistent, and the carboxyl content of the molecular chain is precisely controlled to maintain at the designed low level. This effectively reduces the excessive adsorption and coating of polymer components on the surface of gypsum crystals, avoids defects such as uneven hydration of gypsum and slurry flocculation, and matches the material supply rhythm synchronously throughout the process. Finally, a polycarboxylic acid mother liquor with a concentrated molecular weight range and uniform carboxyl distribution is obtained, which stably ensures that the finished product has both excellent dispersibility and controllable low-retardation characteristics, making it suitable for industrial by-product gypsum with significant impurity fluctuations.

[0077] In one possible implementation, after filtration in the volumetric discharge step, the mixture is stirred and homogenized at room temperature for 25-35 minutes, and then sealed and allowed to stand for 10-14 hours.

[0078] Specifically, after filtration, the material is placed in a room temperature environment and stirred at a speed of 140-170 r / min for 25-35 minutes to homogenize. After homogenization, it is transferred to a sealed container for static curing for 10-14 hours. Even after filtration, there are still trace amounts of unevenly dispersed fine functional component agglomerates in the system. Room temperature low-speed homogenization can promote the full integration of various functional components without destroying the polycarboxylic acid molecular structure, eliminating the phenomenon of local component enrichment. Subsequent long-term sealed static curing allows polycarboxylic acid molecules, organophosphonic acid chelating agents, and various components to form a stable and compatible system, and the molecular forces between components reach equilibrium, avoiding the problem of stratification and precipitation during the storage of the agent. The finished product after this process has a highly uniform distribution of various regulating and dispersing components. When used in industrial by-product gypsum systems, it can simultaneously exert the comprehensive effects of complexation and impurity removal, low-delay setting and water reduction. The agent performance remains consistent with different storage times and different application sites, greatly improving the product's storage stability and the uniformity of the hydration rhythm of the gypsum slurry during on-site application.

[0079] The invention is further illustrated by the following experiments.

[0080] I. Experimental Materials and Equipment

[0081] (a) Experimental materials

[0082] Synthetic raw materials: isopentenyl alcohol polyoxyethylene ether (TPEG), commercially available industrial grade, molecular weight 2400, conforming to GB / T34745-2017; acrylic acid, maleic anhydride, methyl methacrylate, commercially available industrial grade, purity ≥99.5%; ammonium persulfate, sodium hypophosphite, commercially available industrial grade; hydroxyethylidene diphosphonic acid (HEDP), commercially available industrial grade, active ingredient mass fraction 50%; 32% sodium hydroxide aqueous solution, commercially available industrial grade; deionized water, laboratory-made, conductivity ≤5μS / cm.

[0083] Test gypsum raw materials

[0084] Ordinary desulfurized building gypsum: Commercially available calcined finished product, meeting the Grade I requirements of GB / T21371-2019 "Industrial By-product Gypsum for Cement". Basic properties: Standard consistency water requirement 0.58, initial setting time 4.2 min, final setting time 6.0 min, 2-hour flexural strength 2.8 MPa, 2-hour compressive strength 6.9 MPa; Chemical composition (on a dry basis): Calcium sulfate dihydrate ≥92.0%, free calcium oxide 0.25%, soluble sulfate 0.8%, soluble magnesium salt 0.08%, phosphate 0.03%, fluoride ion 0.01%, loss on ignition 6.5%.

[0085] High-impurity desulfurized building gypsum: Commercially available calcined finished product, an industrial by-product gypsum with large impurity fluctuations, simulating the working conditions of inferior by-product gypsum. Basic properties: Standard consistency water requirement 0.62, initial setting time 3.8 min, final setting time 5.5 min, 2-hour flexural strength 2.3 MPa, 2-hour compressive strength 5.7 MPa; Chemical composition (on a dry basis): Calcium sulfate dihydrate ≤83.0%, free calcium oxide 1.32%, soluble sulfate 3.2%, soluble magnesium salt 0.35%, phosphate 0.18%, fluoride ion 0.06%, organic residue 0.45%, loss on ignition 9.2%.

[0086] Benchmarking agents: Commercially available high-retarding-setting polycarboxylate superplasticizer for gypsum (40% solid content) and commercially available low-retarding-setting polycarboxylate superplasticizer for gypsum (40% solid content) are both mainstream commercial products in the building materials market.

[0087] (II) Experimental Instruments and Equipment

[0088] 5L constant temperature sealed stirred reactor (with precision dripping module, micro negative pressure control module, jacket temperature control module, and matching reflux condenser), electronic analytical balance (accuracy 0.0001g), standard cement paste mixer, gypsum flow table tester, Vicat apparatus setting time tester, microcomputer-controlled flexural and compressive strength testing machine, standard constant temperature and humidity curing chamber, precision pH meter, calcium ion selective electrode, and 100-mesh standard test sieve.

[0089] II. Experimental Evaluation Methods and Implementation Standards

[0090] Tests on the fluidity and retention rate of neat cement paste: Referring to GB / T8077-2012 "Test Method for Homogeneity of Concrete Admixtures", the gypsum system was adapted with a fixed water-to-cement ratio of 0.60 and the water-reducing agent dosage was 0.3% of the gypsum powder mass. The initial fluidity of neat cement paste and the fluidity after 30 minutes of standing were tested, and the fluidity retention rate after 30 minutes was calculated to reflect the dispersion stability and anti-flocculation ability.

[0091] Water reduction rate test: Performed in accordance with GB / T8077-2012. The water requirement when the fluidity of blank gypsum paste reaches 180±5mm is used as the benchmark. The water requirement when the water-reducing agent is added to achieve the same fluidity is tested, and the water reduction rate is calculated according to the formula.

[0092] Setting time test: Performed in accordance with GB / T17669.4-1999 "Determination of physical properties of building gypsum paste", test the initial setting and final setting time of the paste, and evaluate the retarding effect of the water-reducing agent.

[0093] Mechanical strength test: The test was conducted in accordance with GB / T17669.3-1999 "Determination of mechanical properties of building gypsum". A standard test strip of 40mm×40mm×160mm was prepared. After standard curing for 2 hours, the flexural and compressive strengths were tested to evaluate the early strength performance and the compatibility with rapid demolding.

[0094] Slurry adhesion level evaluation: Simulating on-site mixing and conveying conditions, the mixed slurry is left to stand in the mixing pot for 10 minutes and then poured out. The degree of adhesion and scaling on the pot wall is observed and divided into 5 levels: Level 0 (clean wall surface with no residue), Level 1 (extremely thin adhesion, can be rinsed with water), Level 2 (thin layer adhesion, can be cleaned by light brushing), Level 3 (local flocculent clumps, requires manual scraping), Level 4 (large area of ​​scaling, difficult to clean), corresponding to the actual pain points of on-site production line shutdown for cleaning of adhesion.

[0095] Free calcium ion complexation rate test: The calcium ion selective electrode method was used to prepare a simulated impurity solution (calcium ion concentration 1200 mg / L, magnesium ion concentration 180 mg / L) that matched the ion concentration of the high-impurity desulfurized gypsum slurry. After adding an equal amount of water-reducing agent, the solution was allowed to stand for 30 min, and the change in the free calcium ion concentration of the system was tested. The free calcium ion complexation rate was calculated to directly characterize the ion complexing ability of the organophosphonic acid chelating agent.

[0096] III. Experimental Procedure

[0097] The specific settings are as follows:

[0098] Baseline formulation and baseline preparation process

[0099] Baseline formulation (by weight, 100% total weight): 22.0% isopentenyl polyoxyethylene ether, 4.8% acrylic acid, 1.2% maleic anhydride, 0.75% methyl methacrylate, 0.42% ammonium persulfate, 0.35% sodium hypophosphite, 1.6% hydroxyethylidene diphosphonic acid, 18.2% 32% sodium hydroxide aqueous solution, and deionized water to bring the total to 100%.

[0100] The standard preparation process is strictly performed according to the optimal process of this invention: S1, the base material is dissolved by stirring at a constant temperature of 62℃; S2, maleic anhydride is completely dissolved and hydrolyzed in water first, then acrylic acid and methyl methacrylate are added to prepare a mixed monomer aqueous solution, and ammonium persulfate aqueous solution and sodium hypophosphite aqueous solution are prepared separately; S3, three sets of liquids are added dropwise at a constant temperature of 62℃ with a drop rate ratio of 5:1:1, and a slight negative pressure of -0.02MPa is maintained throughout the process. The total dropwise addition time is 4 hours, and the polymerization is carried out at the temperature for 2.2 hours after the dropwise addition is completed; S4, the temperature is lowered to 50℃ and an organophosphonic acid chelating agent is added, and the mixture is kept at the temperature for 1.8 hours for curing; S5, the temperature is lowered to 42℃ and sodium hydroxide is added dropwise to adjust the pH to 7.5; S6, water is added to make up the volume, filtered through a 100-mesh filter, and homogenized by stirring at low speed at room temperature for 30 minutes, and then sealed and allowed to stand for 12 hours for curing.

[0101] Module 1: Core Formulation Parameter Optimization and Verification Experiment

[0102] Variable settings: Keep all other formula components, preparation process, and test conditions completely consistent, and use high-impurity desulfurized gypsum as the test substrate. Only adjust the amount of the target component.

[0103] Dosage validation of organophosphonic acid chelating agents

[0104] Example 1-1: The dosage of hydroxyethylidene diphosphonic acid was 1.2%, and the other parameters were completely consistent with the baseline group.

[0105] Examples 1-2: The dosage of hydroxyethylidene diphosphonic acid was 1.6%, and the other parameters were completely consistent with the baseline group.

[0106] Examples 1-3: The dosage of hydroxyethylidene diphosphonic acid was 2.0%, and the other parameters were completely consistent with the baseline group.

[0107] Comparative Example 1-1: Hydroxyethylidene diphosphonic acid component was completely removed, and the reduced amount was made up with an equal amount of deionized water. All other parameters were completely consistent with the baseline group.

[0108] Comparative Examples 1-2: The dosage of hydroxyethylidene diphosphonic acid was 0.8%, and the reduced dosage was made up with an equal amount of deionized water. All other parameters were completely consistent with the baseline group.

[0109] Comparative Examples 1-3: The amount of hydroxyethylidene diphosphonic acid was 2.6%, and the amount of deionized water was reduced accordingly. The other parameters were completely consistent with the baseline group.

[0110] Initiator-chain transfer agent ratio verification

[0111] Examples 1-4: Ammonium persulfate 0.35%, sodium hypophosphite 0.30%, and other parameters were completely consistent with the reference group.

[0112] Examples 1-5: Ammonium persulfate 0.42%, sodium hypophosphite 0.35%, and other parameters were completely consistent with the reference group.

[0113] Examples 1-6: Ammonium persulfate 0.50%, sodium hypophosphite 0.40%, and other parameters were completely consistent with the reference group.

[0114] Comparative Examples 1-4: Ammonium persulfate 0.25%, sodium hypophosphite 0.20%, and other parameters were completely consistent with the reference group.

[0115] Comparative Examples 1-5: Ammonium persulfate 0.60%, sodium hypophosphite 0.50%, and other parameters were completely consistent with the reference group.

[0116] Module 2: Verification of Preparation Process Parameters

[0117] Variable settings: The formula composition was fixed, and the remaining process steps and test conditions were completely consistent. The test substrate was uniformly high-impurity desulfurized gypsum. All reaction vessels in all groups were equipped with reflux condensation devices of the same specifications. Only a single process parameter was adjusted.

[0118] Verification of maleic anhydride dissolution method

[0119] Example 2-1: When preparing the mixed monomer aqueous solution, maleic anhydride was first completely dissolved in water to fully hydrolyze and open the ring, and then acrylic acid and methyl methacrylate were added and mixed and dissolved. The remaining parameters were the same as the reference group.

[0120] Comparative Example 2-1: When preparing the mixed monomer aqueous solution, maleic anhydride, acrylic acid, and methyl methacrylate were added to water simultaneously and mixed and dissolved. The total stirring time was the same as in the example, and the other parameters were the same as in the reference group.

[0121] Copolymer negative pressure condition verification

[0122] Example 2-2: The copolymer was added dropwise while maintaining a slight negative pressure of -0.02 MPa inside the reactor. All other parameters were the same as the baseline group.

[0123] Comparative Example 2-2: The copolymer addition process was carried out in a closed reactor under normal pressure with no negative pressure control. All other parameters were the same as the baseline group.

[0124] Comparative Examples 2-3: The total negative pressure during copolymerization was -0.05 MPa (the negative pressure was too high), and the other parameters were the same as the baseline group.

[0125] Drop acceleration ratio verification

[0126] Examples 2-3: The dropping rate ratio of the mixed monomer aqueous solution, ammonium persulfate aqueous solution, and sodium hypophosphite aqueous solution was 5:1:1, the total dropping time was kept consistent, and the other parameters were the same as the baseline group.

[0127] Comparative Examples 2-4: The dropping rate ratio was 4:1:1 (single dropping was slower), the total dropping time was kept the same, and the other parameters were the same as the baseline group.

[0128] Comparative Examples 2-5: The dropping rate ratio was 6:1:1 (the monomer was dropped faster), the total dropping time was kept the same, and the other parameters were the same as the baseline group.

[0129] Module 3: Comprehensive Performance Comparison and Verification Experiment

[0130] Variable settings: uniform water-reducing agent dosage (converted to solids) of 0.3%, test environment temperature of 20±2℃, and adjustment of gypsum type and water-reducing agent type.

[0131] Blank control group 1: No water-reducing agent was added, and ordinary desulfurized building gypsum was mixed with deionized water only.

[0132] Blank control group 2: No water-reducing agent was added, and only deionized water was used to mix high-impurity desulfurized building gypsum.

[0133] Example 3-1: The water-reducing agent of the present invention was tested using ordinary desulfurized building gypsum.

[0134] Example 3-2: The water-reducing agent of the present invention was tested using high-impurity desulfurized building gypsum.

[0135] Comparative Example 3-1: Commercially available high-retardant-setting polycarboxylate superplasticizer for gypsum was tested using ordinary desulfurized building gypsum.

[0136] Comparative Example 3-2: Commercially available low-retarding polycarboxylate superplasticizer for gypsum, tested using ordinary desulfurized building gypsum.

[0137] Comparative Example 3-3: Commercially available low-retarding polycarboxylate superplasticizer for gypsum, tested using high-impurity desulfurized building gypsum.

[0138] IV. Summary Table of Experimental Results

[0139] Table 1 Results of Experimental Adjustment of Formula Parameters

[0140]

[0141] Table 2. Experimental Results of Key Preparation Process Parameter Verification

[0142]

[0143] Table 3. Results of Comprehensive Performance Comparison Experiment

[0144]

[0145] V. Experimental Results Analysis and Conclusions

[0146] (I) Performance impact of core formulation parameters

[0147] Organophosphonic acid chelating agents are the core components for achieving a balance between anti-flocculation and low-retarding setting. Data on free calcium ion complexation rate directly demonstrates that, within the range of 1.2% to 2.0%, organophosphonic acids can effectively complex 28% to 43% of free calcium ions in the system, simultaneously achieving excellent anti-flocculation effects and controllable retarding: water reduction rate is consistently above 17.5%, fluidity retention rate at 30 minutes is ≥75%, initial setting time is controlled within 8 minutes, and wall adhesion level is consistently at Grade 1.

[0148] When the chelating agent dosage is below the lower limit, the complexing and impurity removal ability is insufficient, and impurity ions consume the effective dispersed components of polycarboxylic acid in advance. The fluidity retention rate drops significantly after 30 minutes, and the slurry wall adhesion grade rises to level 3, which cannot meet the needs of continuous production. When the chelating agent dosage is above the upper limit, excessive complexed calcium ions will significantly inhibit gypsum hydration, prolong the initial setting time to more than 11 minutes, and reduce the strength by more than 30% after 2 hours, thus losing the core advantages of low slow setting and fast demolding.

[0149] The ratio of initiator to chain transfer agent directly determines the molecular weight distribution of the polymer. Within a defined range, polycarboxylic acid products with concentrated molecular weight distribution and regular molecular structure can be synthesized, resulting in balanced water-reducing and retarding properties. If the ratio deviates from the range, the molecular weight distribution will become wider, the water-reducing rate will decrease, the degree of retarding will fluctuate more, and the batch stability of the product will decrease.

[0150] (ii) Performance Influence of Process Parameters

[0151] Maleic anhydride pre-hydrolysis process: Maleic anhydride is first dissolved in water to fully hydrolyze and open the ring, ensuring monomer uniformity and metering accuracy, and avoiding uneven distribution of carboxyl groups in the molecular chain due to incomplete hydrolysis. Compared with the simultaneous dissolution process, the product water reduction rate is increased by 1.3 percentage points, the 30-minute fluidity retention rate is increased by 12.3 percentage points, and the setting time is more uniform, resulting in better batch stability.

[0152] Micro-negative pressure copolymerization process: Micro-negative pressure copolymerization at -0.03~-0.01MPa has a dual effect: firstly, it continuously removes oxygen from the system, weakening the oxygen inhibition effect and making the polymerization reaction stable and controllable throughout, resulting in a narrower polymer molecular weight distribution; secondly, it guides the volatile monomer vapors to flow directionally to the condenser at the top of the reactor, where the monomers are condensed and then flow back to the liquid phase to participate in the reaction, ensuring accurate monomer ratios throughout the reaction. Compared to the atmospheric pressure system, the product's water reduction rate is increased by 1.1 percentage points, and the batch stability of the retarding performance is significantly improved; excessively high negative pressure will remove moisture from the system and disrupt the concentration of the feed solution, leading to a decline in performance.

[0153] Dropping rate ratio control: A dropping rate ratio of 5:1:1 can ensure that the concentrations of monomer, initiator and chain transfer agent are always kept in dynamic balance, and the synthesized polymer molecular structure is the most regular. Deviating from this ratio will lead to an imbalance in the monomer ratio, disordered free radical release rate, and ultimately a decrease in water reduction rate and loss of control over retardation degree.

[0154] (III) Conclusion of Comprehensive Performance Comparison

[0155] Compared with the control group, the water-reducing agent of this invention can increase the fluidity of the slurry from 182mm to 282mm in ordinary desulfurized gypsum, with a water reduction rate of 20.5%. At the same time, the initial setting is delayed by only 2.6 minutes, and the strength increases instead of decreasing after 2 hours. It has excellent water-reducing effect and extremely low retarding side effect.

[0156] In high-impurity desulfurized gypsum, this product exhibits minimal performance degradation, maintaining a fluidity retention rate of nearly 80% after 30 minutes, with a wall adhesion grade only rising to level 2. In contrast, commercially available low-retardant water-reducing agents show a sharp drop in dispersion stability in high-impurity systems, with a fluidity retention rate of less than 42% after 30 minutes and a wall adhesion grade reaching level 4, making them completely unsuitable for continuous production. While commercially available high-retardant products offer good dispersion stability, their setting time is extended by more than three times, and their 2-hour strength is only about 60% of the control group, making them unsuitable for rapid demolding production of precast components.

[0157] The formulation component dosage range and preparation process parameters defined in this invention have sufficient experimental rationality and engineering applicability. Through the synergistic effect of low carboxyl molecular structure design, narrow molecular weight distribution regulation, low-dose chelation anti-impurity mechanism, and trace hydration regulation, it achieves comprehensive performance of high water reduction, low retardation, strong anti-impurity, early strength and fast demolding. It solves the industry pain points of traditional gypsum water-reducing agents such as slow setting, poor anti-impurity ability, and inability to adapt to the continuous production of industrial by-product gypsum, and has good industrial application value.

[0158] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A low-deceleration carboxylic acid gypsum water-reducing agent, characterized in that, By weight percentage, including: The composition is: isopentenyl alcohol polyoxyethylene ether 20.0~24.0, acrylic acid 4.0~5.5, maleic anhydride 1.0~1.5, methyl methacrylate 0.6~0.9, persulfate 0.35~0.50, sodium hypophosphite 0.30~0.40, organophosphonic acid chelating agent 1.2~2.0, sodium hydroxide aqueous solution 17.0~19.5, with the balance being deionized water. The sum of the weight percentages of all components is 100%.

2. The low-deceleration carboxylic acid gypsum water-reducing agent according to claim 1, characterized in that, The persulfate is one of ammonium persulfate, sodium persulfate, or potassium persulfate.

3. The low-deceleration carboxylic acid gypsum water-reducing agent according to claim 1, characterized in that, The organophosphonic acid chelating agent is at least one of 2-aminotrimethylenephosphonic acid, hydroxyethylidene diphosphonic acid, and ethylenediaminetetramethylidene phosphonic acid.

4. The low-deceleration carboxylic acid gypsum water-reducing agent according to claim 1, characterized in that, The persulfate has a particle size range of 80 mesh to 120 mesh; The sodium hypophosphite has a particle size range of 100 mesh to 140 mesh.

5. A method for preparing a low-deceleration carboxylic acid gypsum water-reducing agent, characterized in that, The method for preparing the low-coagulation carboxylic acid gypsum water-reducing agent according to any one of claims 1 to 4 comprises the following steps: Bottom material dissolution: Add the specified amount of isopentenyl alcohol polyoxyethylene ether and part of deionized water to the reactor, heat to 60~65℃, and stir until completely dissolved to obtain the bottom material liquid; Preparation of solutions: Prepare a mixed monomer aqueous solution containing acrylic acid, maleic anhydride and methyl methacrylate, a first aqueous solution containing persulfate, and a second aqueous solution containing sodium hypophosphite. Copolymerization reaction: The bottom liquid in the reactor is continuously controlled at 60~65℃, and the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution are simultaneously added dropwise to the bottom liquid in the reactor; after the addition is completed, the temperature is maintained for polymerization for 2~2.5h to obtain polycarboxylate mother liquor; Low-temperature curing: The polycarboxylic acid mother liquor in the reactor is cooled to 45~55℃, and the appropriate amount of organophosphonic acid chelating agent is added to the reactor. The mixture is kept warm and stirred for 1.5~2 hours. Neutralization and stabilization: Cool the material in the reactor to 40~45℃, add the appropriate amount of sodium hydroxide aqueous solution to the reactor and adjust the pH to 7.2~7.8; Volumetric discharge: Add the remaining deionized water to the reactor, homogenize, filter, and obtain low-coagulation carboxylic acid gypsum water-reducing agent.

6. The method for preparing the low-deceleration carboxylic acid gypsum water-reducing agent according to claim 5, characterized in that, In the liquid preparation step, when preparing the mixed monomer aqueous solution, maleic anhydride is first completely dissolved in water, and then acrylic acid and methyl methacrylate are added and mixed to dissolve.

7. The preparation method of the low-deceleration carboxylic acid gypsum water-reducing agent according to claim 5, characterized in that, During the copolymerization reaction, the reactor is kept under negative pressure throughout the synchronous dropwise addition process, with a negative pressure value of -0.03 to -0.01 MPa.

8. The method for preparing the low-deceleration carboxylic acid gypsum water-reducing agent according to claim 5, characterized in that, In the copolymerization reaction step, the dropping rate ratio of the mixed monomer aqueous solution, the first aqueous solution, and the second aqueous solution is 5:1:

1.

9. The preparation method of the low-deceleration carboxylic acid gypsum water-reducing agent according to claim 5, characterized in that, After filtration in the volumetric discharge step, stir and homogenize at room temperature for 25-35 minutes, then seal and let stand for 10-14 hours.